Law in the New Era of Emerging Technologies: Can Creation Made by an Artificial Intelligence be Protected by Copyright? - Sinaga, Joy Febe Ismikesasta; Novendra, Bayu (UKInstitute, 2023)
Despite the fact that Artificial Intelligence (AI) has a long history in the twentieth and twenty-first centuries, there are many unsolved challenges. AI is a rapidly growing, promising area of research that is reaching its prime. Contemporarily, AI is used in a wide range of tasks, from virus detection, e-commerce chat boxes, to law-making. Subsequently, AI is not only designed to perform a particular and limited task (Narrow AI), but also to generate new creations based on cognitive skills and advancements in that spectrum (General AI). The topic discussed further in this paper is the second type of AI. This paper will attempt to answer the following questions. First, can creation made by an AI be protected by copyright? Second, who is the creator of the creations made by an AI? Third, how do we determine the holders of moral rights and economic rights for creations made by an AI? This paper used legal research, emphasizing literature study. In so doing, the data were analyzed with the deductive method to construct conclusions. This paper shows that creations made by an AI can be protected with copyright, with the creator being the person or people who contribute the most to the basic code of the AI, as well as the training data used, so that the creation can be produced. Furthermore, the person as creators also become moral rights holders and economic rights holders.